2007
DOI: 10.1021/pr060525b
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Proteomic Analysis of Arabidopsis thaliana Using Alternative Solubilization Techniques

Abstract: This study presents a comparative proteomic analysis of the membrane subproteome of whole Arabidopsis seedlings using 2% Brij-58 or 60% methanol to enrich and solubilize membrane proteins for strong cation exchange fractionation and reversed-phase liquid chromatography-tandem mass spectrometry (LC-MS/MS). A total of 441 proteins were identified by our Brij-58 method, and 300 proteins were detected by our methanol-based solubilization approach. Although the total number of proteins obtained using the nonionic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 63 publications
4
72
0
Order By: Relevance
“…Membrane Localization of AtNCL in Planta-AtNCL was reported to be localized to the vacuole by prediction and proteomics strategy (62)(63)(64)(65). In this study, p35S::AtNCL-YFP was constructed and transformed into Arabidopsis, the signal in the AtNCL-YFP transgenic seedlings was stronger near the plasma membrane after plasmolysis (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Membrane Localization of AtNCL in Planta-AtNCL was reported to be localized to the vacuole by prediction and proteomics strategy (62)(63)(64)(65). In this study, p35S::AtNCL-YFP was constructed and transformed into Arabidopsis, the signal in the AtNCL-YFP transgenic seedlings was stronger near the plasma membrane after plasmolysis (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Accordingly, it appears that, as for CA1, CA2 has retained its ancestral C 3 role in C 4 plants. Interestingly, cytosolic b-CAs have been found associated with the plasma membranes of several plant species (Utsunomiya and Muto, 1993;Santoni et al, 1998;Kawamura and Uemura, 2003;Alexandersson et al, 2004;Mongrand et al, 2004;Benschop et al, 2007;Mitra et al, 2007), and AtbCA4 specifically localizes to Arabidopsis cell membranes (Fabre et al, 2007). Mongrand et al (2004) showed that tobacco plasma membrane lipid rafts were enriched in a cytosolic b-CA and an aquaporin, NtAQP1, which has CO 2 transport activity (Uehlein et al, 2003) and decreases the resistance of the envelope to CO 2 (Uehlein et al, 2008).…”
Section: F Pringlei Ca2 Encodes a Cytosolic Enzymementioning
confidence: 99%
“…Unfortunately, neither REF4 nor RFR1 has been identified in any of the proteomic studies performed to date (e.g., Alexandersson et al 2004;Marmagne et al 2004;Dunkley et al 2006;Morel et al 2006;Hartman et al 2007;Heazlewood et al 2007;Lanquar et al 2007;Mitra et al 2007). The Aramemnon database for plant membrane spanning proteins (Schwacke et al 2003) annotates REF4 and its homologs as having between 10 to 12 transmembrane regions (TMRs), although for any individual protein, less than half of these score above a cutoff score of 0.5.…”
Section: à9mentioning
confidence: 99%